Method for improving electrode resistance uniformity of alternating current electroluminescent device

By optimizing the ratio of luminescent powder to PB glue and adjusting the surface roughness of the luminescent layer, the problem of uneven electrode resistance of the AC electroluminescent device is solved, and the service life and photoelectric performance of the device are significantly improved.

CN119865941APending Publication Date: 2025-04-22ANHUI UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510011458.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art has failed to fully optimize the surface roughness of the light emitting layer of the alternating electroluminescent device, resulting in high uneven electrode resistance, affecting the light emitting stability and service life of the device.

Method used

By optimizing the ratio of luminescent powder to PB glue, adjusting the surface roughness of the luminescent layer, and forming a uniform dielectric layer and luminescent layer through screen printing technology, finally forming an upper electrode layer and device package.

Benefits of technology

It effectively reduces the resistance unevenness of silver nanowire film electrodes, improves the electrical performance of electroluminescent devices, significantly extends the service life of the device, and improves brightness and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119865941A_ABST
    Figure CN119865941A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the electrode resistance uniformity of an AC electroluminescent device, and the preparation method of a complete ACEL device comprises the following steps: uniformly spraying a metal nanowire electrode material on the surface of a substrate to form a bottom electrode with uniform resistance and excellent conductivity; a bottom electrode is sequentially covered with a dielectric layer material and a light-emitting layer material through the screen printing technology, the surface of the light-emitting layer is further sprayed with a layer of metal nanowire electrode material to construct an upper electrode, finally, the upper electrode is covered with a packaging material through screen printing to protect a device, the whole process is simple in technology, high in repeatability and reliability, and the manufacturing cost is low. Wherein the surface roughness of the light-emitting layer affects the electrical performance of a metal nanowire electrode, the long-term stability of the electrode is reduced due to high roughness, and the service life of the electrode is further shortened, so that the surface roughness of the light-emitting layer is controlled by adjusting the solid content of the fluorescent powder in the light-emitting layer, which is very important for improving the performance and the stability of a device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of research on performance of alternating current electroluminescent devices, and more specifically relates to a method for improving the uniformity of electrode resistance of an alternating current electroluminescent device. Background Art

[0002] Alternating current electroluminescent devices (ACEL) are widely used in the fields of displays, lighting equipment and indicator lights. The performance of ACEL devices, especially the brightness stability and service life, are affected by the performance of each layer in its structure. ACEL devices usually include a bottom electrode layer, a dielectric layer, a light-emitting layer and an upper electrode layer. The bottom electrode layer generally uses a silver nanowire film or other conductive materials, the dielectric layer commonly uses BaTiO3, and the upper electrode layer generally uses a transparent conductive material such as a silver nanowire film. The preparation process of these layers is relatively mature in the prior art and does not constitute an innovative part of the present invention.

[0003] However, in ACEL devices, the preparation process of the light-emitting layer has an important influence on the overall performance of the device. In particular, the ratio of the light-emitting powder to the binder directly affects the roughness of the surface of the light-emitting layer, which in turn affects the resistance uniformity of the silver nanowire thin film electrode. The existing technology fails to fully optimize the surface roughness of the light-emitting layer, resulting in a large non-uniformity in the electrode resistance, which affects the luminescence stability and service life of the device. Summary of the invention

[0004] The present invention provides a method for improving the uniformity of electrode resistance of an AC electroluminescent device to solve the above technical problem.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for improving the uniformity of electrode resistance of an AC electroluminescent device comprises the following steps:

[0007] Spray-coating AgNWs on the substrate to form a bottom electrode;

[0008] Screen-printing a mixture of BaTiO3 and PB glue on the bottom electrode, which forms a dielectric layer after curing;

[0009] Screen printing a mixture of phosphor and PB glue on the cured dielectric layer to form a light-emitting layer after curing;

[0010] coating the AgNWs solution on the light-emitting layer to form an upper electrode layer;

[0011] The uniformly mixed PDMS solution is screen-printed on the AgNWs upper electrode layer for device packaging.

[0012] Preferably, in the step of spraying AgNWs electrode material on the substrate to form a bottom electrode, the concentration of AgNWs dispersed in water is 2 mg / ml, the length of AgNWs is 50-60 um, the diameter is 90-100 nm, and the thickness of the AgNWs bottom electrode is 100-500 nm.

[0013] Preferably, a mixture of BaTiO3 and PB glue is screen-printed on the bottom electrode, and in the step of forming a dielectric layer after curing, the dielectric layer is evenly coated on the bottom electrode layer by spin coating, scraping, or screen printing, and cured by heat treatment or UV curing. The solid content of the mixture of BaTiO3 and PB glue is 50%, the particle size of BaTiO3 is 0.5-2um, and the thickness of the dielectric layer is 7-20um.

[0014] Preferably, a mixture of phosphor and PB glue is screen-printed on the cured dielectric layer, and in the step of forming a light-emitting layer after curing, the light-emitting layer is composed of phosphor and PB glue, and the phosphor layer is provided with two layers. The solid content of the first layer of the mixture of phosphor and PB glue is 50%, and the solid content of the second layer of the mixture of phosphor and PB glue is 0-60%. The particle size of the phosphor is 20-28um, and the thickness of the light-emitting layer is 10-15um.

[0015] Compared with the prior art, the present invention has at least the following advantages:

[0016] 1. The present invention optimizes the ratio of luminescent powder to PB glue, effectively reduces the surface roughness of the luminescent layer, reduces the resistance non-uniformity of the silver nanowire thin film electrode, and improves the electrical performance of the electroluminescent device;

[0017] 2. By improving the resistance uniformity and the surface roughness of the light-emitting layer, the present invention significantly extends the service life of the device. The test results show that the optimized device has less brightness attenuation during long-term use and has higher stability;

[0018] 3. The optimized light-emitting layer provides a more uniform electric field distribution, improves the brightness and stability of electroluminescent devices, and meets the needs of modern display technology for efficient and long-lasting light sources;

[0019] 4. The optimization method adopted by the present invention is simple and easy to implement, does not require complicated equipment and process improvements, has high industrialization prospects, and can be applied in large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 a, SEM image of AgNWs electrode diameter; b, SEM image of AgNWs electrode length; c, distribution diagram of AgNWs electrode diameter; d, distribution diagram of AgNWs electrode length;

[0021] Figure 2 Based on the screen printing of a light-emitting layer with a phosphor solid content of 50% on the dielectric layer: a. SEM image of the cross section of the light-emitting layer with a phosphor solid content of 50% after screen printing; b. SEM image of the cross section of the light-emitting layer with a phosphor solid content of 33% after screen printing; c. SEM image of the cross section of the light-emitting layer with a phosphor solid content of 25% after screen printing;

[0022] Figure 3 On the basis of screen printing a light-emitting layer with a phosphor solid content of 50% on the dielectric layer: a. SEM image of the cross-section of the light-emitting layer with a phosphor solid content of 0% and 1-2 layers of pure PB glue screen-printed; b. 3D microscope photo of a light-emitting layer with a phosphor solid content of 50% screen-printed; c. 3D microscope photo of a light-emitting layer with two phosphor solid content of 0% screen-printed;

[0023] Figure 4 a. Curves showing the variation of NUF and light attenuation rate of the upper electrode of ACEL device with the solid content of phosphor in the light-emitting layer; b. The square resistance distribution of the upper electrode when the solid content of phosphor in the light-emitting layer is 33%; c. The square resistance distribution of the upper electrode when the solid content of phosphor in the light-emitting layer is 50%;

[0024] Figure 5 a. SEM image of the AgNWs electrode after ACEL device failure when the solid content of the phosphor in the light-emitting layer is 50%; b. SEM image of the AgNWs electrode after ACEL device failure when the solid content of the phosphor in the light-emitting layer is 33%. DETAILED DESCRIPTION

[0025] In order to more clearly understand the above-mentioned objects, features and advantages of the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other. In the following description, many specific details are set forth in order to fully understand the present invention, and the embodiments described are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the art without making creative work are within the scope of protection of the present invention.

[0026] Comparative Example 1

[0027] A method for improving the uniformity of electrode resistance of an AC electroluminescent device, specifically, comprising the following steps;

[0028] Step 1: Spray a 2 mg / ml AgNWs solution onto a 125 um thick PET substrate and bake it in an oven at 80° C. for 10 min to form a bottom electrode.

[0029] Step 2: BaTiO3:PB glue in the dielectric layer is mixed in a ratio of 1:1, and a uniform mixture is formed after ultrasonic dispersion and defoaming treatment. Then a layer is screen-printed on the bottom electrode in step 1, and baked in an oven at 110°C for 10 minutes to form a dielectric layer.

[0030] Step 3: The solid content of phosphor in the mixture of phosphor and PB glue is 50%. After ultrasonic dispersion and defoaming treatment, a uniform mixture is formed. Then, two layers of luminescent layers are screen-printed on the dielectric layer in step 2, and baked in an oven at 110°C for 10 minutes to form a luminescent layer.

[0031] Step 4: Spray 2 mg / ml AgNWs solution to cover the light-emitting layer in step 3, place in an oven at 80° C. and bake for 10 min to form an upper electrode.

[0032] Step 5: Screen-print the evenly mixed PDMS solution above the AgNWs upper electrode layer, bake it in an oven at 110°C for 10 minutes, and then package the device.

[0033] Example 1

[0034] A method for improving the uniformity of electrode resistance of an AC electroluminescent device comprises the following steps: spraying and covering AgNWs on a substrate to form a bottom electrode; screen printing a mixture of BaTiO3 and PB glue on the bottom electrode to form a dielectric layer after curing; screen printing a mixture of phosphor and PB glue on the cured dielectric layer to form a luminescent layer after curing; coating an AgNWs solution on the luminescent layer to form an upper electrode layer; screen printing a uniformly mixed PDMS solution on top of the AgNWs upper electrode layer to perform device packaging to prevent environmental factors from affecting device performance.

[0035] The preparation method of the AC electroluminescent device is the same as the preparation process of Comparative Example 1, except that the proportion of phosphor in the second light-emitting layer is 40%, and it is screen-printed on the first light-emitting layer and baked in an oven at 110°C for 10 minutes to form a light-emitting layer. The upper electrode layer usually uses a silver nanowire film or other conductive material, which is coated on the surface of the light-emitting layer by a preparation method similar to that of the bottom electrode layer, and is cured to ensure its good conductivity and transparency. The transmittance of the AgNWs electrode is 87-95%.

[0036] Figure 1 b is a cross-sectional SEM image of Example 1 of the present invention. The surface roughness is reduced compared with that when the solid content of the phosphor is 50%, the NUF is 18.31%, and the light attenuation rate of the ACEL device is 28.75% at a voltage of 130V for 3 hours. The change in the solid content of the phosphor can effectively reduce the surface roughness of the light-emitting layer, optimize the NUF of the AgNWs electrode on the surface of the light-emitting layer, and reduce the light attenuation rate of the ACEL device.

[0037] Example 2

[0038] The preparation method of the AC electroluminescent device is the same as that of Comparative Example 1, except that the proportion of the phosphor in the second light-emitting layer is 33%, and the phosphor is screen-printed on the first light-emitting layer. The device is placed in an oven at 110° C. and baked for 10 minutes to form a light-emitting layer.

[0039] Figure 2 c is a cross-sectional SEM image of Example 2 of the present invention. The surface roughness is further improved compared with the case where the phosphor solid content is 40%, and the surface is significantly flattened. Figure 4 a is the curve of the change of NUF and light attenuation rate of the upper electrode of the ACEL device of Example 2 of the present invention with the solid content of the phosphor in the light-emitting layer, the NUF is 15.83%, and the light attenuation rate of the ACEL device at 130V for 3h is 20.32%. Compared with the comparative example 1, the light attenuation rate of the ACEL device at 130V for 3h is reduced by 14.38%. Figure 4 a is the square resistance distribution of the upper electrode when the solid content of the phosphor in the light-emitting layer of Example 2 of the present invention is 33%, and the square resistance distribution is 9.15-18.7Ω.

[0040] Example 3

[0041] The preparation method of the AC electroluminescent device is the same as that of Comparative Example 1, except that the proportion of the phosphor in the second light-emitting layer is 0%, and the screen printing is performed on the first light-emitting layer. The device is placed in an oven at 110° C. and baked for 10 minutes to form a light-emitting layer.

[0042] Figure 3 a is the cross-sectional SEM of the light-emitting layer of Example 3 of the present invention, which proves that screen-printing a layer of PB glue on the light-emitting layer with a phosphor content of 50% can significantly improve the surface roughness of the light-emitting layer, but the surface still has uneven areas, and its electrode NUF is: 19.32%.

[0043] Example 4

[0044] The preparation method of the AC electroluminescent device is the same as that of the comparative example 1, except that the uneven surface of the light-emitting layer in Example 3 is further optimized, the proportion of phosphor in the second and third light-emitting layers is 0%, and screen printing is performed on the second light-emitting layer. The light-emitting layer is placed in an oven at 110°C and baked for 10 minutes to form a light-emitting layer.

[0045] Figure 3 a is a SEM image of the surface after screen printing two layers of PB glue in Example 4 of the present invention. As can be seen from the figure, the surface roughness is greatly reduced, and a basically planar structure is formed. Figure 3c is Example 4 of the present invention, which is a 3D microscope picture of the surface of the light-emitting layer of Example 4 of the present invention. It can be seen that the surface undulation height is 0-6.2um, which is 25.2um lower than the undulation height of Comparative Example 1.

[0046] Figure 1 ab are the SEM images of the diameter and length of the AgNWs electrode used in the present invention. The diameter and length are statistically analyzed, and the average diameter is (96±4.77) nm, and the average length is (55±7.17) um. Figure 2 a is a cross-sectional SEM image of the ACEL device of comparative example 1 of the present invention, and it can be clearly seen that the surface roughness is relatively large. Figure 3 b is a 3D microscope photo of the ACEL device in comparative example 1 of the present invention, the surface fluctuation reaches 31um, Figure 4 a are respectively the variation curves of the non-uniformity factor (NUF) of comparative example 1 of the present invention with the solid content of the phosphor in the light-emitting layer and the variation curves of the light attenuation rate with the solid content of the phosphor in the light-emitting layer. When the phosphor content is 50%, the NUF is 41%, and the light attenuation rate of the ACEL device at 130V voltage for 3h is 34.7%, Figure 4 c is the square resistance distribution of the upper electrode when the solid content of the phosphor in the luminescent layer of comparative example 1 of the present invention is 50%, and the square resistance distribution is 10.8-30.9Ω, Figure 5 a is a SEM picture of the upper electrode AgNWs when the ACEL device of comparative example 1 of the present invention fails. It can be seen that large-area damage and fracture occur on the surface of the AgNWs. When the ACEL device fails, the surface roughness of the light-emitting layer of the AgNWs electrode is relatively large, which reduces the contact area between the AgNWs electrode and the light-emitting layer, and reduces the stability and photoelectric performance of the AgNWs electrode.

[0047] The present invention provides a method for optimizing the surface roughness of a light-emitting layer by adjusting the ratio of a light-emitting powder to an adhesive, and further improving the resistance uniformity of a silver nanowire thin film electrode, thereby significantly improving the photoelectric performance and service life of an AC electroluminescent device. When preparing the light-emitting layer, the surface roughness of the light-emitting layer is controlled by adjusting the mass ratio of the light-emitting powder to the adhesive. An appropriate ratio can significantly reduce the roughness of the light-emitting layer and reduce the resistance non-uniformity of the silver nanowire thin film electrode. After the resistance uniformity is improved, the electroluminescence efficiency and stability of the device are improved, and ultimately a longer service life is achieved.

[0048] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the above preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for improving the uniformity of electrode resistance of an AC electroluminescent device, characterized in that: The following steps are involved: Spray-coating AgNWs on the substrate to form a bottom electrode; Screen-printing a mixture of BaTiO3 and PB glue on the bottom electrode, which forms a dielectric layer after curing; Screen-printing a mixture of phosphor and PB glue with a solid content of 0-60% of phosphor on the cured dielectric layer to form a light-emitting layer with different roughness after curing; coating the AgNWs solution on the light-emitting layer to form an upper electrode layer; The uniformly mixed PDMS solution is screen-printed on the AgNWs upper electrode layer for device packaging.

2. A method for improving the uniformity of electrode resistance of an AC electroluminescent device according to claim 1, characterized in that: In the step of spraying AgNWs electrode material on the substrate to form a bottom electrode, the concentration of AgNWs dispersed in water is 2 mg / ml, the length of AgNWs is 50-60 um, the diameter is 90-100 nm, and the thickness of the AgNWs bottom electrode is 100-500 nm.

3. A method for improving the uniformity of electrode resistance of an AC electroluminescent device according to claim 1, characterized in that: In the step of screen-printing a mixture of BaTiO3 and PB glue on the bottom electrode and forming a dielectric layer after curing, the dielectric layer is evenly coated on the bottom electrode layer by spin coating, scraping, and screen printing, and cured by heat treatment or ultraviolet light curing. The solid content of the mixture of BaTiO3 and PB glue is 50%, the particle size of BaTiO3 is 0.5-2um, and the thickness of the dielectric layer is 7-20um.

4. A method for improving the uniformity of electrode resistance of an AC electroluminescent device according to claim 1, characterized in that: In the step of screen-printing a mixture of phosphor and PB glue on a cured dielectric layer to form a light-emitting layer after curing, the light-emitting layer is composed of phosphor and PB glue, and the phosphor layer is provided with two layers. The solid content of the first layer of phosphor and PB glue mixture is 50%, and the solid content of the second layer of phosphor and PB glue mixture is 0-60%. The particle size of the phosphor is 20-28um, and the thickness of the light-emitting layer is 10-15um.

Citation Information

Cited By

  • Display device and electronic apparatus

    US12622159B2

  • Display device and electronic apparatus

    US20240074292A1